Kepemimpinan pada Manajemen Mutu Terpadu Pendidikan Islam di MTs. Al-Ma’tuq Cisaat Sukabumi - Abdul Hakim Zawawi; Maemunah Sa’diyah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Leadership is a major factor in social life, especially its involvement in organizations or institutions. The influence of leadership will direct the management under it to have good quality. This study examines Leadership in Total Quality Management based on Islamic education at MTs Al-Ma'tuq Cisaat, Sukabumi. With a data collection model and literature study by taking five types of Islamic leadership, this study concludes that the practice of leadership in Islamic education quality management at MTs Al-Ma'tuq has been running effectively and is still being developed. However, an assessment survey of management performance and its importance is still needed so that it can become a benchmark for development in a better direction.